Interobserver variations in the delineation of target volumes and organs at risk and their impact on dose distribution in intensity-modulated radiation therapy for nasopharyngeal carcinoma. - Peng, Ying-lin; Chen, Li; Shen, Guan-zhu; Li, Ya-ning; Yao, Ji-jin; Xiao, Wei-wei; Yang, Lin; Zhou, Shu; Li, Jia-xin; Cheng, Wan-qin; Guan, Ying; Xia, Hai-qun; et al. (Oral Oncology, 2018)
Objective: This study aimed to (a) assess the differences in the delineation of target volumes and organs-at-risk (OARs) by different physicians designing an intensity-modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC) and (b) analyze the impact of these differences on the treatment plan optimization.Materials and Methods: The planning target volumes (PTVs) and OARs for radiotherapy were manually delineated from computed tomography images of a patient with NPC, and a standard delineation was determined using the STAPLE algorithm of ABAS software. IMRT was designed using one standard plan and 10 individual plans based on the same constraints and field conditions. The maximum/minimum ratio (MMR) of the PTV and OAR volumes and the coefficient of variation (CV) for the different groups were evaluated and compared to the volume of the standard contour.Results: Significant differences were seen in the PTVs of the nasopharynx (PTVnx), neck lymph node (PTVnd) and the OARs manually delineated by different physicians. Compared to the standard plan, the mean dose-related parameters of various OARs in different individual plans were not significantly different, while that of most organs in different individual plans were reduced. However, a significant difference in the dose at each organ was noted in different individual plans.Conclusion: Significant differences were noted in the PTV and OAR delineations by different physicians in radiotherapy of NPC, and their dosimetric parameters were significantly different from the standard planned parameters. Therefore, multicenter trials should pay attention to the impact of these differences on the clinical evaluation.